Perancangan Model Akuntansi Pokok untuk Menyusun Laporan Keuangan Berdasarkan SAK EKMKM - Lulu Raihana Fakhira; Arie Apriadi Nugraha (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to design a basic accounting model that can assist Usaha Bumbu Kita in the organization of various transactions, forms, and records to produce financial reports that present accurate and detailed financial information. This study uses a qualitative research method with a case study approach. Data collection techniques were carried out using participatory observation, interviews, and documentation. The results of the study indicate that Usaha Bumbu Kita does not have a financial recording and reporting system by accounting principles yet. In this study, proposals for financial recording and reporting are given by designing an organizational structure, a list of accounts, accounting policies, supporting documents, a flowchart that includes the sales, purchase, and preparation of financial statements. In addition, this research also produces a financial report for the April 2021 period that is following the provisions of SAK EMKM as a recommendation material to the manager of Usaha Bumbu Kita.